Answer:
4(k - 3)(3k + 5)
Step-by-step explanation:
Given
12k² - 16k - 60 ← factor out 4 from each term
= 4(3k² - 4k - 15) ← factor the quadratic
Consider the factors of the product of the coefficient of the k² term and the constant term which sum to give the coefficient of the k term
product = 3 × - 15 = - 45 , sum = - 4
Factors are - 9 and + 5
Use these factors to split the middle term
3k² - 9k + 5k - 15 → ( factor the first/second and third/fourth terms
= 3k(k - 3) + 5(k - 3) ← factor out (k - 3)
= (k - 3)(3k + 5)
Hence
12k² - 16k - 60 = 4(k - 3)(3k + 5) ← in factored form
Let's do this step by step:
Subtract both sides by 7
-2|x-4|= -10
Divide each side by -2
|x-4|= 5
Now since this is an absolute value equation, you will have two answers. This means you make the equation both positive and negative.
X-4= 5and -(x-4)= 5
Solve for x for both
X-4= 5: add four on both sides
X= 9
-x+ 4= 5: subtract 4 and divide by -1
X= -1
So your answer is: X= -1 , 9
From 17 x 17. to simplify, (1/2(17)(17) x tan A)
Answer:
its letter c its (3,4) I hope this help
Answer:
<u><em>0.006 cents</em></u>
Step-by-step explanation:
divide 1.20 with 200
since a unit price is 1 of something
so 1.20 divided by 200 = 0.006 cents.
0.006 is your answer.